Study of the Thermodynamic Functions of the Adsorption of Safranin Dye from Water Using Cellulose after Loading it with Silver Nanoparticles Prepared by the Green Method - Hussein, Atheer Ali Salem; Alwan, Liqaa Hussain (American Journal of Bioscience and Clinical Integrity, 2025)
Silver nanoparticles were prepared using a plant extract obtained from the leaves of the La Niña tree, where the extract was used as a natural reducing agent due to its content of flavonoids and antioxidants. The nanoparticles were synthesized through the reaction of silver nitrate with the plant extract under controlled thermal conditions with continuous stirring. These particles were characterized using FT-IR, EDX, SEM, and XRD techniques, which confirmed the formation of silver nanoparticles with Ag–O bonds and an average size of approximately 18.5 nanometers. Spectral analyses showed the presence of organic functional groups remaining from the plant extract. Additionally, the adsorption of Safranin dye on the surface of cellulose loaded with the nanoparticles was studied. The maximum wavelength of the dye was determined at 518 nanometers, and calibration curves were prepared to determine dye concentrations. The study showed that the adsorption equilibrium time was reached within 20–25 minutes, with a high adsorption efficiency (about 92% without nanoparticles, and 85.5% with their presence). Thermal analyses indicated that the adsorption process was exothermic and spontaneous, with negative entropy changes reflecting an increase in order during adsorption. These results suggest the effectiveness of using the plant extract in preparing environmentally friendly silver nanoparticles and their ability to enhance the adsorption properties of cellulose for dye removal from aqueous solutions.